SPATIAL ANALYSIS IN CONSERVATION SITU IN BANTEN PROVINCE: CASE STUDY OF SITU KADUPAYUNG, PANDEGLANG REGENCY, BANTEN - Taufik, Isvan; Sudrajat, Endang; Gemilang, Meysa Cahya (Department of Civil Engineering, Faculty of Engineering, Universitas Islam Malang, 2023)
Spatial planning analysis is a way to identify the location and area of a site based on spatial structure and spatial patterns. The research aims to discuss Spatial Analysis of Site Conservation in Banten Province: Case Study of Situ Kadupayung, Pandeglang Regency, Banten. The research method uses survey methods and uses Geographic Information System (GIS) analysis, as well as site area and contour analysis methods. The research results show that the area based on the KIB in Situ Kadupayung is 40,000 m². From the results of GPS RTK measurefments, it is known that the area of Situ Kadupayung is 34,462 m2 / 3.44 Ha. The difference between the measurement results and the goods inventory card (KIB) data at Situ Kadupayung is -5.538 m² / -0.55 Ha. There are 2 (two) factors that can cause large differences between Goods Inventory Card (KIB) data, namely 1) Internal Factors: Measurement techniques used (methods and tools); Errors in inputting measurement results data; 2) External Factors: Natural Factors, namely sedimentation, and Non-Natural Factors (Society). Keywords: Spatial Analysis; Conservation Situ; Banten Province